Data structures & other objects using Java - Main, Michael
Takes a gentle approach to learning data structures using the Java programming language. Providing an early, self-contained review of object-oriented programming and Java, this text gives readers a firm grasp of key concepts and allows those experienced in another language to adjust easily. It has a solid foundation in building and using abstract data types, along with an assortment of advanced topics such as B-trees for project building and graph. It incorporates Java 5.0 including the use of scanner class and generic data types (generics)